Theacrine, a purine alkaloid derived from Camellia assamica var. kucha, ameliorates impairments in learning and memory caused by restraint-induced central fatigue - Yi-Fang Li; Min Chen; Chen Wang; Xiao-Xiao Li; Shu-Hua Ouyang; Chi-Chi He; Zhong-Fu Mao; Bun Tsoi; Hiroshi Kurihara; Rong-Rong He (Journal of Functional Foods, 2015)
Camellia assamica var. kucha is a local tea in the Yunnan province of China and people there believe its intake can relieve fatigue and their tiredness. Theacrine, a lesser-known purine alkaloid, was first discovered in this kind of tea. Here, we found that theacrine (15 mg/kg) could be absorbed into the blood and pass across the blood–brain barrier after oral administration. The effect and mechanism of theacrine on central fatigue were examined by employing a restraint stress model in mice. Results of behavioral tests suggested that oral administration of theacrine (5, 10, 15 mg/kg) significantly reversed learning and memory impairment caused by central fatigue. In addition, levels of fatigue-related neurotransmitters in the brains of restraint mice, including 5-hydroxytryptamine and dopamine as well as their metabolites, were restored by theacrine. Further, we found that the anti-fatigue effect of theacrine was associated with the regulation of brain glucose metabolism and the inhibition of phosphodiesterases.